(untitled) (مجلة إحالات, 2026)
In unclaimed letters carried by the postman, literary self turns to the art of writing as a form of catharsis for its inner complexities. Our study, titled « writing for the self and Escaping the pandemic, A Reading of Unclaimed metters by Rawiya Yahyawi » sheds light on the impact of COVID-19 on the author’s psyche and her endeavor to conront this pandemic through her literary writing, narrating stories from her past with family . we have concluded that the nature and essence of these letters differ from other literary genres as they convey the chemistry of the emotional impulse driving the act of writing.